Marketing Strategy and Referral Efforts from First Level Health Facilities (FKTP) to Diponegoro National Hospital through the 7P (Product, Price, Place, Promotion, People, Process, and Physical Environment) - Jati, Sutopo Patria; Fatmasari, Eka Yunila; Risdanti, Syafira; Silavati, Yuni Adhita (Universitas Aisyah Pringsewu, 2021)
Rumah Sakit Nasional Diponegoro (RSND) services are still not optimal, seen from the indicators of BOR, TOI and patient dissatisfaction, its need for an appropriate marketing strategy. So it needed an appropriate marketing strategy. The purpose was to analyze internal factors (weaknesses) and external factors (opportunities and threats) in determining marketing strategies and referral efforts to RSND with a qualitative analytic descriptive approach. The research was analysis 7P marketing mix (product, price, place, promotion, people, process, and physical evidence) with informants FKTP, DPP, Directors, Public Relations and Marketing, supervisory board, patients of RSND and university. Good perceptions on superior service products, service quality and prices, groups and skills of professionals, and sophisticated level of facilities and the image of RSND as an education hospital are strengths of the hospital. However, service schedules haven't in accordance with user expectations, the process and marketing team wasn't had reached all groups, communication between FKTPs and the hospital, and inefficient registration procedures are weaknesses. The strategy needed was market penetration and product development. The strategic priorities should be implemented providing media information and promotion regarding types of services to be distributed to FKTPs and holding networking forums between FKTPs and RSND.Abstrak: Pelayanan Rumah Sakit Nasional Diponegoro(RSND)masih belum optimal dilihat dari indikator BOR, TOI dan ketidakpuasan pasien sehingga perlu adanya upaya strategi pemasaran yang tepat. Tujuan penelitian ini adalah menganalisis faktor internal (kekuatan dan kelemahan) dan faktor eksternal (peluang dan ancaman) dalam penentuan strategi pemasaran dan upaya rujukan ke RSND dengan desain kualitatif dan pendekatan deskriptif analitik. Penelitian menganalisis bauran pemasaran 7P (product, price, place, promotion, people, process, dan physical evidence, dengan narasumberFKTP, DPP, Direksi, Humas dan Pemasaran, dewan pengawas dan pasien RSNDserta pihak universitas.Persepsi cukup baik pada produk layanan unggulan, kualitas dan harga layanan, ketersediaan dan keterampilan tenaga profesional, ketersediaan fasilitas yang canggih serta citra RSND sebagai rumah sakit pendidikanmenjadi sisi kekuatan rumah sakit. Jadwalpelayanan kurang sesuai ekspektasi pengguna, proses dan tim marketing yang belum menjangkausemua kalangan, komunikasi antara FKTP dengan pihak rumah sakit, dan prosedur pendaftaran yang kurang efisien menjadi kelemahan. Strategi yang diperlukan yaitu penetrasi pasar dan pengembangan produk .Prioritas strategi yang sebaiknya dijalankan yaitu menyediakan media informasi dan promosi mengenai jenis layanan untuk dibagikan ke FKTP dan mengadakan forum jejaring antara FKTP dengan RSND.